The known species of the genus Achagua Rindge, 1983, with the description of three new species from the Neotropics (Geometridae: Ennominae) - Matson, Tanner A. (Zootaxa, 2023)
The previously monotypic geometrid genus Achagua (Ennominae: Nacophorini) is reviewed following the discovery of three undescribed species. New species are as follows: A. cooperae n. sp. described from Costa Rica, A. magna n. sp. described from Ecuador, Peru, and Bolivia; and Achagua velata n. sp. described from French Guiana. Available COI barcode data is briefly reviewed, and adult and genitalic illustrations are provided for each of the four known species.